Eating Girls: Deleuze and Guattari’s Becoming-Animal and the Romantic Sublime in William Blake’s Lyca Poems - Heymans, Peter (Humanimalia, 2011)
This article argues that Deleuze and Guattari’s concept of becoming-animal is aesthetically as well as structurally related to the discourse of the sublime. It investigates the species politics of both concepts and illustrates their ecocritical potential with an analysis of William Blake’s Lyca poems, “The Little Girl Lost” and “The Little Girl Found,” both published in his Songs of Innocence and of Experience (1794).